Toward Addressing the Challenge to Predict the Heat Capacities of RDX and HMX Energetic Materials. Issue 8 (11th March 2022) - Sorescu, Dan C.; Larentzos, James P.; Rice, Betsy M.; Brennan, John K.
Abstract: Availability of heat capacity as a function of pressure and temperature is an essential prerequisite for development of a computational multiscale strategy capable to address the evolution of microstructure and energy release in advanced high energy density materials. In the case of 1, 3, 5‐trinitro‐1, 3, 5‐triazinane (RDX) and 1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocane (HMX) systems as two of the most studied energetic materials, there are substantial gaps in experimental data, with available heat capacities values distributed only in a region close to standard ambient conditions. In this study we demonstrate how these major experimental limitations can be addressed in the case of the RDX and HMX systems based on the combined use of classical and quantum mechanical calculations. We show that by considering ideal gas properties evaluated using quantum mechanical methods, and residual properties obtained from molecular simulations using fully flexible atomistic force field models, excellent agreement can be obtained for the predicted heat capacities to the most recent experimental values. An important advantage of the current computational methodology is that it allows evaluation of both constant‐volume and constant‐pressure heat capacities for a broad interval of temperatures and pressures, which encompasses solid and liquid phases conditions. In the case of the solid α and γ phases of RDX and the β phase of HMX, the predicted results follow closely both the available experimental data at standard ambient conditions and the results obtained using density functional theory calculations at high pressures, a regime where experimental data are not available. A perspective to expand the current methodology is also discussed. Abstract :